2008
DOI: 10.1038/ijo.2008.142
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal preventive-screening cutoffs for metabolic syndrome in adolescents

Abstract: Objective: To detect metabolic risk factor cutoff points in adolescence for the diagnosis of metabolic syndrome that develops at the age of 17 years (MS 17 ). Design: This study adopted a 6-year design incorporating four data collection time points (TPs). Volunteers were assessed prospectively at the ages of 12, 13, 14 and 17. Participants: A total of 210, 204, 198 and 187 schoolchildren volunteered at the first (TP 1 ¼ 12 years old), second (TP 2 ¼ 13 years old), third (TP 3 ¼ 14 years old) and fourth (TP 4 ¼… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 33 publications
(49 reference statements)
1
25
0
4
Order By: Relevance
“…In our sample, the HS subjects had a similar prevalence rate of MetSyn (5.7%) compared with the College subjects (8.5%). When compared with the general population, the prevalence of MetSyn in this group of adolescent athletes is similar to that reported in other findings (8) but is slightly lower than that reported by Flouris et al (12) who found that 16% of a population of 17-year-old boys diagnosed with MetSyn. Given the increase in the obesity rate among adolescents (21), it is certainly possible that the MetSyn rate in the general adolescent population is higher than that observed among the HS football players in the current study.…”
Section: Discussionsupporting
confidence: 83%
“…In our sample, the HS subjects had a similar prevalence rate of MetSyn (5.7%) compared with the College subjects (8.5%). When compared with the general population, the prevalence of MetSyn in this group of adolescent athletes is similar to that reported in other findings (8) but is slightly lower than that reported by Flouris et al (12) who found that 16% of a population of 17-year-old boys diagnosed with MetSyn. Given the increase in the obesity rate among adolescents (21), it is certainly possible that the MetSyn rate in the general adolescent population is higher than that observed among the HS football players in the current study.…”
Section: Discussionsupporting
confidence: 83%
“…There is controversy as to which body composition indices are the best when screening youths and adults for cardio metabolic risk, with some studies suggesting the use of body mass index ( BMI) or body fat (BF) percentage (%) 4 while others suggesting waist circumference (WC) and skinfolds 5 .…”
Section: Introductionmentioning
confidence: 99%
“…The literature suggests that the fundamental components of MS are overweight, physical inactivity, and genetic predisposition to develop IR [15]. It has been pointed out that, among these risk factors, excessive body fat is the main cause of this syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…A consensus definition of MS in children and adolescents is important as it would allow researchers to assess biological, social, and environmental covariates, document secular trends, and investigate the syndrome's stability over time and its association with mortality risk. This information could result in a better understanding of the MS etiology, as well as a more timely identification and evaluation of new strategies for prevention and intervention [15]. …”
Section: Introductionmentioning
confidence: 99%